Cost-Effective Strategy and Feasibility for Amylase Production from Okara by Bacillus subtilis J12 - Muhamad Khairi Mahfudz; Somchai Jaikhan; Konlarat Phirom-on; Jirawan Apiraksakorn (Fermentation, 2024)
Low-cost enzyme production is considered a feasibility factor in enzyme commercialization. Okara, a high-nutritional agro-industrial residue from soybean processing, was performed as a medium for bacterial amylase production to save costs and increase productivity. This study aimed to produce, characterize, activate amylase, and evaluate the material cost for media from okara. Under solid-state fermentation (SSF) of okara without pretreatment, Bacillus subtilis J12 could produce 983 U/g of amylase within 24 h. Bacillus subtilis J12 amylase had optimal activity at pH 6.0 and 50 °C and was stable at a moderate temperature for up to 120 min. Identified as a metalloenzyme, the activity was improved by ferric ions. The purification of amylase resulted in two fractions which contained at least two types of amylases. Compared with other producers, the production was evaluated using low-cost media without additional supplementations. Based on the productivity, characteristics, and evaluation, Bacillus subtilis J12 amylase was potentially commercialized, had economic value, possessed energy-saving features, and could be applied for industrial use.